Bridging the Employability Gap: Rethinking Curriculum Relevance at IAIN Sultan Amai Gorontalo - Mujahid Damopolii; Yowan Tamu; Herson Anwar; Asyifa Nadia Jasmine; Kusumawati Daeng Matara (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2026)
A persistent global gap exists between higher education curricula and the evolving competency demands of the digital workforce, particularly in Islamic universities in developing countries, where curriculum transformation lags. While extant employability and outcome-based education (OBE) literature has extensively examined graduate competencies as predictors of work readiness, limited attention has been given to how institutional curriculum inertia functions as a mediating mechanism that perpetuates employability mismatches, especially within Islamic higher education contexts where epistemological orientations integrate disciplinary knowledge with moral and spiritual values. This study addresses this gap by investigating the misalignment between curricular structures and labor market needs at IAIN Sultan Amai Gorontalo, Indonesia. Using a qualitative case study approach, data were collected through document analysis and in-depth interviews with 15 stakeholders, including deans, department heads, alums, and employers. The findings reveal that curriculum inertia operates through three interconnected mechanisms: (1) cognitive dominance in curriculum design that allocates 70-80% of credit hours to theoretical content; (2) pedagogical path dependency that perpetuates lecture-based instruction at the expense of experiential learning; and (3) institutional decoupling between curriculum review processes and evolving digital industry demands. These mechanisms collectively produce graduates' insufficient work readiness and high employment mismatch, evidenced by over 50% of alums working outside their academic disciplines. This study contributes to employability and OBE literature by proposing the Curriculum Inertia-Employability Mismatch Model, which theorizes curriculum inertia as an institutional mediating mechanism between curriculum design and graduate work readiness. The model advances OBE frameworks by demonstrating that competency-based curriculum principles alone are insufficient without addressing institutional inertia that constrains their implementation. Practically, the study recommends adaptive curriculum redesign, structured industry partnerships, and enhanced internship and soft skills programs to disrupt curriculum inertia and enhance graduate competitiveness in the digital era.